Valores de hemoglobina durante el embarazo y su relación con el tipo de parto y peso de los recién nacidos centro materno perinatal – Tarapoto Enero a Diciembre del 2006 - Rengifo Vargas, Ana Luisa (2008)
He objective of the present research was determine, through relations statistics, the correspondence that exist between the value of hemoglobin (Hgb) in the pregnant with the type of delivery and the weight of them newly born in patients that is attended in the Center maternal Perinatal-Tarapoto in the period understood between January and December of the 2006. The methodology followed corresponds to WI retrospective descriptive study - correlaciona\; carried out in the service of gynaecology and obstetrics of the Center maternal Perinata1-Tarapoto. The study sample was 330 pregnant women discussed delivery in that Center. We used a card of collection of data validated by the test of the reliability of the Pearson coefficient. The given sample was characterized by 88% (290 pregnant) ended her pregnancy in a labour at term whereas 98% (322 pregnant women) received iron supplement during your pregnancy. The results of hemoglobin in blood, the gestant...